Higher predicted type 2 diabetes risk is associated with worse mental health and self-rated general health among adults without known diabetes in Germany – Results of the nationwide population-based study GEDA 2022 - Laura Neuperdt; Yong Du; Julia Nübel; Ulfert Hapke; Lena Walther; Gert B. M. Mensink; Almut Richter; Christa Scheidt-Nave; Jens Baumert; Christin Heidemann (PLoS ONE, 2025)
Objective There is increasing evidence that the link between type 2 diabetes (T2D) and mental health may be partly due to shared modifiable risk factors. The present study examined whether a higher predicted T2D risk is associated with poorer self-rated general health (SRH) and mental health (SRMH) as well as depressive and anxiety symptoms among adults without diagnosed diabetes. Methods Analyses are based on cross-sectional data from 4,909 adults (18 + years) without known diabetes who participated in the nationwide telephone interview survey German Health Update (GEDA) 2022. The predicted 5-year T2D risk (in %) was assessed with the German Diabetes Risk Score (GDRS) and categorized into very low (<2%), low (2- < 5%), elevated (5- < 10%) and high (≥10%) risk groups. Poisson regression was used to calculate prevalence ratios (PRs) of SRH, SRMH, depressive and anxiety symptoms according to T2D risk categories and models were adjusted for sex, age, education, region, living alone, and social support. Results Predicted T2D risk (95% confidence interval (CI)) was very low for 60.8% (58.7–63.0%), low for 15.7% (14.2–17.2%), elevated for 10.7% (9.5–12.1%), and high for 12.8% (11.5–14.2%) of adults. Compared to those with very low T2D risk, participants at high T2D risk were less likely to report very good/good SRH (PR; 95% CI: 0.65; 0.56–0.75) or excellent/very good SRMH (0.65; 0.51–0.81) and more likely to have depressive (2.48; 1.70–3.63) or anxiety symptoms (2.50; 1.54–4.05). Conclusion Findings underline that physical and mental health should be considered together in the context of prevention and health promotion strategies.